ANALISIS MODEL ALTMAN Z-SCORE UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA BANK YANG LISTING DI BEI TAHUN 2010 – 2013 - Ayik Rizky Ariesco (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
This study aims to determine the financial condition of banks listed on the Indonesia Stock Exchange from 2010 - 2013. By using the Altman Z-Score to see how much financial distress at every bank, amounting to 27 banks. By using the formula Z-Score = 1.2 + 1.4 X1 X2 X3 + 0.6 + 3.3 + 1.0 X4 X5. The results showed a total of 27 banks that went public there are still some who are greeting bankrupt condition. In 2010, as many as 41 percent of banks declared bankrupt, 7 percent gray area, and 52 percent declared healthy. In 2011, as many as 48 percent of the bank is declared bankrupt, 11 percent gray area, and 41 percent declared healthy. In 2012, as many as 56 percent of the bank is declared bankrupt, 11 percent gray area, and 33 percent declared healthy. In 2013, as many as 56 percent of the bank was declared bankrupt, 7 percent gray area, and 37 percent declared healthy. Keywords: Altman Z-Score, financial distress